Targeting Metabolic Dysregulation in Alzheimer’s Disease: A Potential Therapeutic Strategy - Barnwal, Nivedita; Dubey, Sonal; Tiwari, Prashant (Current Drug Metabolism, 2025)
Alzheimer’s disease (AD), the most common form of dementia, is characterized by progressive cognitive decline and neuropathological hallmarks, including amyloid-beta plaques and tau tangles. Emerging evidence implicates metabolic dysfunction as a critical contributor to the pathogenesis and progression of AD. Impaired glucose metabolism, mitochondrial dysfunction, oxidative stress, and lipid dysregulation are frequently observed in AD brains, suggesting that metabolic dysfunction may exacerbate neurodegeneration and cognitive deficits. This review explores the therapeutic potential of targeting metabolic pathways to mitigate AD pathology. Key metabolic disruptions, including insulin resistance, reduced cerebral glucose utilization, and mitochondrial inefficiency, are closely linked to neuronal energy deficits and synaptic dysfunction. Therapeutic approaches, such as insulin sensitizers, ketogenic diets, and mitochondrial-targeted antioxidants, have shown promise in preclinical and early clinical studies. Additionally, strategies to modulate lipid metabolism, such as enhancing cholesterol efflux via APOE or reducing neurotoxic ceramides, offer potential avenues for intervention. The review also highlights the roles of neuroinflammation and oxidative stress as mediators of metabolic dysfunction in AD, underscoring the need for multifaceted approaches that target both metabolic and inflammatory pathways. The emerging field of precision medicine offers opportunities to tailor interventions based on individual metabolic profiles, potentially enhancing treatment efficacy. Despite the growing recognition of metabolic dysfunction in AD, translating these insights into effective therapies remains challenging due to the disease’s complexity and heterogeneity. Future research must focus on elucidating the interplay between metabolic pathways and AD pathology, identifying reliable biomarkers, and designing targeted interventions. By addressing the metabolic underpinnings of AD, this review underscores the potential of metabolic reprogramming as a novel and integrative therapeutic strategy to slow or prevent disease progression and improve patient outcomes.
Keywords: neurodegeneration